Industrial Relations and Social Dialogue in the Age of Collaborative Economy (IRSDACE). National report: Slovakia - Sedláková, Mária (Bratislava, 2018)
"In this report you find the country case study for Slovakia within the IRSDACE project. Following the methodology of the IRSDACE project, this report first provides an overview of the platform work in Slovakia, its place in the Slovak labour market and in industrial relations in Slovakia. Second, it analyses discourse on platform economy among established industrial relations actors in three sectors: accommodation, personal transportation and microwork. Third, it provides a unique empirical evidence of discourse among platform owners and platform workers in three sectors. Fourth, it analyses implications of workers’ experience with the platform economy for industrial relations and social dialogue in Slovakia."